Magneto-sensitive liposomes containing manganese ferrite nanoparticles as nanocarriers for new promising antitumor thienopyridin-amine derivatives - Rodrigues, Ana Rita Oliveira (2016)
In this work, manganese ferrite (MnFe2O4) nanoparticles, with superparamagnetic behaviour at room temperature, were obtained by coprecipitation method and their structural and magnetic properties were evaluated. New promising antitumor drugs, thienopyridine derivatives containing an amine moiety and were successfully incorporated in aqueous and solid magnetoliposomes.